Die Verletzung der Unterhaltspflicht gemäß § 170 I StGB Legitimationsprobleme der Strafbarkeit im Kontext von Zivilrechtsakzessorietät, Vorfragenkompetenz und problematischen Rechtsfolgen - zugleich ein Beitrag zur Verwertbarkeit von Steuerdaten - Höhne, Lara (Schriften zum Strafrecht (SR), 2024)
»The Violation of Maintenance Obligation According to Section 170 I StGB. Legitimacy Problems of Criminal Liability in the Context of Accessoriness of Civil Law, Competence of Preliminary Questionings and Problematic Legal Consequences - also a Contribution to the Usability of Tax Data«: The study deals with the legal interest that is protected by section 170 I of the Criminal Code and the thereby related legitimacy of a penalty. Furthermore the binding effect of civil court decisions as well as concrete consequences of criminal liability are adressed. In addition, the existing investigative instruments for determining the maintenance debtor's ability to pay are discussed and a possible use of tax data in proceedings according to section 170 I StGB is proposed de lege ferenda.